2003
DOI: 10.1161/01.str.0000087149.42294.8c
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Different Subtypes of Stroke in China

Abstract: Background and Purpose-The goal of this article is to clarify the proportion of stroke subtypes in China, where stoke is the most common cause of death. Methods-A total of 16 031 first-ever strokes in subjects Ն25 years of age were identified in 1991 to 2000 from 17 Chinese populations through a community-based cardiovascular disease surveillance program in the China Multicenter Collaborative Study of Cardiovascular Epidemiology. World Health Organization diagnosis criteria were used for classification of stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
4
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(213 citation statements)
references
References 38 publications
11
193
4
4
Order By: Relevance
“…In the APCSC, individuals from Asia and those with diabetes experienced a relatively greater rate of haemorrhagic stroke than those from ANZ and those without diabetes. However, an interpretation of the public health and clinical implications of this finding must take into consideration the evolving epidemiology of CVD in the Asia-Pacific region, with a rapidly increasing predominance of atherothrombotic conditions in many areas [15][16][17][18]. For example, during the 1990s, the incidence rate of haemorrhagic stroke in China declined by an average of 12% per year, while that of ischaemic stroke increased by at least 5% per year in most regions [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the APCSC, individuals from Asia and those with diabetes experienced a relatively greater rate of haemorrhagic stroke than those from ANZ and those without diabetes. However, an interpretation of the public health and clinical implications of this finding must take into consideration the evolving epidemiology of CVD in the Asia-Pacific region, with a rapidly increasing predominance of atherothrombotic conditions in many areas [15][16][17][18]. For example, during the 1990s, the incidence rate of haemorrhagic stroke in China declined by an average of 12% per year, while that of ischaemic stroke increased by at least 5% per year in most regions [19].…”
Section: Discussionmentioning
confidence: 99%
“…The data of 2000, from Beijing, Shanghai, Changsha, three major cities of the information, reveal that the incidence of stroke is from 76.1 to 150.0/10 million, and ICH accounted for 18.9-47.6% of all stroke cases (8). Another study including more information from more cities showed that ICH accounted for 17.1-39.4% in subtypes of stroke (21). In Western populations, ICH accounted for a rate of 6.5% to 19.6% and the annual incidence rate is 20.9-28.0/10 million.…”
Section: Ich In China Mainlandmentioning
confidence: 98%
“…In Western populations, ICH accounted for a rate of 6.5% to 19.6% and the annual incidence rate is 20.9-28.0/10 million. The average mortality rate after 1 month of ICH is 40.4%, of which Japan has 16 .7%, the lowest in the world, and China 49.4%, higher than the world average (1,21). Chinese populations are rapidly adopting Western dietary habits, including increased energy intake, fat intake, and alcohol consumption, and decreased physical activity and cigarette smoking in recent years, together with China's economic development.…”
Section: Ich In China Mainlandmentioning
confidence: 99%
“…Further details about the study populations have been reported elsewhere. 12,13 All participants signed consent forms.…”
Section: Study Populationsmentioning
confidence: 99%